2016
DOI: 10.1016/j.jpedsurg.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Bowel dysfunction following pullthrough surgery is associated with an overabundance of nitrergic neurons in Hirschsprung disease

Abstract: PURPOSE Recent evidence suggests that patients with Hirschsprung disease (HD) have abnormal neurotransmitter expression in the ganglionated proximal colon. These alterations may cause persistent bowel dysfunction even after pullthrough surgery. We sought to quantify the proportion of nitrergic neurons in the ganglionic colon of HD patients and relate these findings to functional outcome. METHODS The proximal resection margin from 17 patients with colonic HD who underwent a pullthrough procedure and colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Since the proportion of nitrergic neurons in these mice can be modulated by antibiotics-induced dysbiosis in a temporal manner (Figs 4 and 5), our work calls for detailed characterization of the distal ENS as a function of age and exposure to antibiotics not only in HSCR mouse models but also in human HSCR patients. Indeed, given that the proportion of nitrergic neurons is increased in HSCR patients as well 41 , this could have a direct influence on how these patients are being taken care of.…”
Section: Discussionmentioning
confidence: 99%
“…Since the proportion of nitrergic neurons in these mice can be modulated by antibiotics-induced dysbiosis in a temporal manner (Figs 4 and 5), our work calls for detailed characterization of the distal ENS as a function of age and exposure to antibiotics not only in HSCR mouse models but also in human HSCR patients. Indeed, given that the proportion of nitrergic neurons is increased in HSCR patients as well 41 , this could have a direct influence on how these patients are being taken care of.…”
Section: Discussionmentioning
confidence: 99%
“…The only current treatment is the operative removal of the segment devoid of ENS. However, recent studies suggested that the remaining bowel, although considered healthy, presents also ENS defects such as altered proportion of nitrergic neurons 27 , and that these defects could contribute to intestinal dysmotility that persists even after the surgery in many HSCR patients. In the current study, we determined the expression and distribution of Sema3A and its receptor NRP1 in the rat developing gut and studied the role of Sema3A on neuronal connectivity.…”
mentioning
confidence: 99%
“…Only recently, Cheng et al observed changes in nNOS neurons in the proximal resection margin of HSCR patients. These changes were characterised by an increased proportion of nNOS myenteric neurons (nNOS +/Tuj + neurons) as compared to “controls” 13 . When expressed in proportion of neurons (normalised to the total number of neurons), we also observed an increased proportion of nNOS neurons in HSCR patients as compared to ARM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, the proportion of nNOS neurons was significantly reduced in HSCR patients with OS as compared to HSCR patients without OS. Cheng et al showed that the increased proportion of nNOS neurons in HSCR patients was retrospectively associated with non-stratified postoperative complications, including indifferently constipation, HAEC and faecal incontinence 13 . These differences between our studies result from the fact that they did not stratify patients according to the nature of postoperative complications (OS, HAEC or diarrhoea, that are discriminated by the proportion of nNOS neurons in our study).…”
Section: Discussionmentioning
confidence: 99%